Pain intensity rating training: results from an exploratory study of the ACTTION PROTECCT system. Issue 5 (May 2016) - Smith, Shannon M.; Amtmann, Dagmar; Askew, Robert L.; Gewandter, Jennifer S.; Hunsinger, Matthew; Jensen, Mark P.; McDermott, Michael P.; Patel, Kushang V.; Williams, Mark; Bacci, Elizabeth D.; Burke, Laurie B.; Chambers, Christine T.; et al.
Abstract : Abstract: Clinical trial participants often require additional instruction to prevent idiosyncratic interpretations regarding completion of patient-reported outcomes. The Analgesic, Anesthetic, and Addiction Clinical Trial Translations, Innovations, Opportunities, and Networks (ACTTION) public–private partnership developed a training system with specific, standardized guidance regarding daily average pain intensity ratings. A 3-week exploratory study among participants with low-back pain, osteoarthritis of the knee or hip, and painful diabetic peripheral neuropathy was conducted, randomly assigning participants to 1 of 3 groups: training with human pain assessment (T+); training with automated pain assessment (T); or no training with automated pain assessment (C). Although most measures of validity and reliability did not reveal significant differences between groups, some benefit was observed in discriminant validity, amount of missing data, and ranking order of least, worst, and average pain intensity ratings for participants in Group T+ compared with the other groups. Prediction of greater reliability in average pain intensity ratings in Group T+ compared with the other groups was not supported, which might indicate that training produces ratings that reflect the reality of temporal pain fluctuations. Results of this novel study suggest the need to test the training system in a prospective analgesic treatment trial. Abstract : Supplemental Digital Content is Available in the Text.The ACTTION PROTECCT training system for 0 to 10 average pain intensity numerical rating scale led to modest benefits. Further research in a prospective treatment trial is needed.